An Efficient Synthesis of Katsube Nitrile: A Key Building Block for Eburnamine-Vincamine Alkaloids - Chen, Xiaofei; Chen, Fener (Synthesis, 2014)
A novel synthesis of the Katsube nitrile is achieved via an efficient diastereoselective Pictet–Spengler cyclization of 3-ethyl-2-hydroxy-1-[2-(1H-indol-3-yl)ethyl]-6-oxopiperidine-3-carbonitrile to construct the cis-[CD] rings in 1-ethyl-4-oxo-1,2,3,4,6,7,12,12b-octahydroindolo[2,3-a]quinolizine-1-carbonitrile, and 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD) catalyzed condensation of tert-butyl 4-cyano-4-(hydroxymethyl)hexanoate with tryptamine to assemble 4-cyano-4-(hydroxymethyl)-N-[2-(1H-indol-3-yl)ethyl]hexanamide as the key steps.
Keywords: eburnamine-vincamine alkaloids; Katsube nitrile; Pictet–Spengler cyclization; cis-diastereoselectivity; 1,5,7-triazabicyclo[4.4.0]dec-5-ene